INVESTIGATE THE DEMAND OF GREEN TALENTS OF SMART MACHINERY INDUSTRY IN SOUTHERN TAIWAN - Lin, Chin-Chiuan; Chen, Li-Jung (International Journal of Application on Economics and Business, 2025)
Green talents play a key role in enterprises, especially when enterprises face the challenges of sustainable development and net zero emissions. For enterprises, the net zero emissions issues need to consider the relationship between environmental sustainability, social responsibility, and the enterprise's economic interests. The present study conducted questionnaire survey and in-depth interview to investigate the demand of green talents of smart machinery industry in southern Taiwan. According to the results of questionnaire survey and in-depth interview, the demand of green talents of smart machinery industry generally focuses on environmental safety and energy conservation managers. However, most enterprises do not have high demand for new green talents. Basically, most of the new manpower added by enterprises after transformation is based on existing personnel being sent out for training. In terms of operational function requirements. First of all, they focus on energy management, energy conservation, carbon reduction, and inventory. Secondly, information skills, communication skills, and legal aspects are also key knowledge. Most of the interviewed enterprises have no streamlined manpower planning in terms of promoting net zero emissions.